Gender sensitivity of barangay officials in local governance in the Municipality of Zarraga - Bayogos, Nindi; Eguilos, Melanie; Lasola, Ma. Theresa Ruby; Paglumotan, Zhara
Executive Summary-Gender-sensitive officials are important to attain a society that is free from racism, sexism and oppression, especially on women. The objective of this study is to identify whether the barangay officials of the Municipality of Zarraga are gender sensitive or non-gender sensitive in their local governance. Through descriptive research, variables such as age, civil status, sex, educational attainment and length of service were analyzed to find out if these affects to the awareness of the barangay officials to gender issues and concerns. The results of the study based on the data gathered revealed several fact: (1) gender sensitivity is dependent of age; (2) gender sensitivity is dependent of civil status; (3) gender sensitivity is independent of sex; (4) gender sensitivity is dependent of educational attainment; and, (5) gender sensitivity id dependent of length of service. Based on the fndings, the researchers came up with the following recommendations: (1) institutionalization of gender sensitivity training and workshops; (2) re-educate both men and women; (3) thrust for gender sensitive barangay officials; and (4) development for both men and women.